Smart charging schedule of plug-in electric vehicles for voltage support: A prosumer-centric approach - Singh S.; Verma M.K. (My University, 2025)
A centralized technique for load scheduling of Plug-in Electric Vehicles (PEVs) is proposed in this work. In this approach, various scenarios of integrating PEVs to the grid and operating constraints are considered. Maximum charging and discharging rates, State of Charge (SOC) limits, security limits on the node voltages, and charging requirements of PEV owners have been accounted for as constraints. The proposed technique aims to reduce the charging cost of PEVs and utilize the available Distributed Energy Resource (DER) of PEVs to provide ancillary service of voltage support. Three different cases are simulated with a Time of Use (TOU) tariff structure. The proposed PEV charge scheduling technique is tested on a practical IEEE low voltage distribution system. Further, the proposed scheme is validated for real-time application using a Real-Time Digital Simulator (RTDS) with Real-Time Automation Controller (RTAC) communicating over industry protocols (DNP3 and IEC-61850 GOOSE). © 2022 Elsevier Ltd